Structural Basis of Outstanding Multivalent Effects in Jack Bean α‐Mannosidase Inhibition. (6th June 2018) - Howard, Eduardo; Cousido‐Siah, Alexandra; Lepage, Mathieu L.; Schneider, Jérémy P.; Bodlenner, Anne; Mitschler, André; Meli, Alessandra; Izzo, Irene; Alvarez, H. Ariel; Podjarny, Alberto; Compain, Philippe
Abstract: Multivalent design of glycosidase inhibitors is a promising strategy for the treatment of diseases involving enzymatic hydrolysis of glycosidic bonds in carbohydrates. An essential prerequisite for successful applications is the atomic‐level understanding of how outstanding binding enhancement occurs with multivalent inhibitors. Herein we report the first high‐resolution crystal structures of the Jack bean α‐mannosidase (JBα‐man) in apo and inhibited states. The three‐dimensional structure of JBα‐man in complex with the multimeric cyclopeptoid‐based inhibitor displaying the largest binding enhancements reported so far provides decisive insight into the molecular mechanisms underlying multivalent effects in glycosidase inhibition.